Isolation and purification of a new enamide biosurfactant from Fusarium proliferatum using rice-bran. Issue 67 (24th July 2015) - Bhardwaj, Garima; Cameotra, Swaranjit Singh; Chopra, Harish Kumar
<x xml:space="preserve">Abstract</x> A new fungus Fusarium proliferatum was isolated from the oil contaminated sludge of the rice-bran oil industry, which was capable of producing biosurfactants when grown on rice-bran.